1996
DOI: 10.1080/09670269600651161
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and systematics ofBatrachospermum(Batrachospermales, Rhodophyta) in North America. 8a. SectionBatrachospermum:Batrachospermum gelatinosum

Abstract: Eighty-six populations of Batrachospermum gelatinosum were examined from th~'oughout its known range in North America and were compared using nqultivariate morphometrics and image analysis. Morphological variability was as great in individual populations as that measured among locations. Populations pooled for each biome showed a north-south trend in whorl and carpogonium size. The mean measurements for the tundra were significantly smaller in whorl diameter and larger in carpogonium size than those for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
2
10
0
2
Order By: Relevance
“…In North America, B. gelatinosum has a wide distribution occurring from the tundra in the North to the southeastern coastal plain in the South and appears to be present in streams of varying physical and chemical parameters (Vis et al 1996). The ranges in morphological characters showed some trends when pooled by biome with smaller whorl diameter and larger carpogonium size in the tundra as compared with the coastal plain.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In North America, B. gelatinosum has a wide distribution occurring from the tundra in the North to the southeastern coastal plain in the South and appears to be present in streams of varying physical and chemical parameters (Vis et al 1996). The ranges in morphological characters showed some trends when pooled by biome with smaller whorl diameter and larger carpogonium size in the tundra as compared with the coastal plain.…”
Section: Introductionmentioning
confidence: 91%
“…The ranges in morphological characters showed some trends when pooled by biome with smaller whorl diameter and larger carpogonium size in the tundra as compared with the coastal plain. In that same paper, the researchers showed that specimens from Newfoundland and Rhode Island had almost as much variation in various morphological characters measured throughout the year in three streams as was recorded across the geographic range (Vis et al 1996). A phylogeographic study of this taxon in eastern North America found little genetic variation throughout most of its geographic range, but again specimens were plastic in their morphology (house et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geralmente, por representarem sistemas geograficamente isolados, as nascentes podem apresentar numerosos táxons endêmicos, como, por exemplo, de macroalgas (e.g. Vis & Sheath 1996). Contudo, de acordo com Necchi Júnior (1992), esta flora não é tão diferente daquela encontrada em ambientes de águas correntes.…”
Section: Introductionunclassified
“…Estudos ficológicos envolvendo nascentes são escassos mundialmente, sendo que, os poucos existentes se concentram na América do Norte (Whitford 1956, Leake & Leake 1961, Vis & Sheath 1996, Sherwood & Sheath 1999, Sherwood et al 2000 …”
Section: Introductionunclassified